Gold nanoparticle embedded hydrogel matrices as catalysts: better dispersibility of nanoparticles in the gel matrix upon addition of N-bromosuccinimide leading to increased catalytic efficiency - Ramtenki, Vilas; Anumon, V. D.; Badiger, Manohar V.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2012)
A simple and convenient method for generating and immobilizing gold NPs into polyethylene glycol-polyurethane (PEGPU) matrices is presented. The gold NP immobilized PEGPU (Au NP-PEGPU) hydrogel matrices are easy to handle and can be used as catalysts. The efficiency, reusability and durability of the Au NP-PEGPU catalyst matrices were investigated using the reduction of 4-nitroaniline (4NA) to p-phenylenediamine (p-PDA) by sodium borohydride in the presence of the catalyst as a test reaction. The Au NPs in the PEGPU matrix got aggregated after 3 cycles of catalysis but dispersion could be regenerated by the addition of N-bromosuccinimide (NBS). After this regeneration process the Au NPs-PEGPU matrix showed excellent efficiency without any aggregation, leaching or degradation. The reusability of the catalyst for 28 cycles yielding a total turnover number of 3220 and turn over frequency of 0.152 s(-1) is demonstrated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: catalysis; hydrogels; Immobilization; Nanoparticles; Turn over numbers

Synthesis of Ag-glyconanoparticles using C-glycosides, their lectin binding studies and antibacterial activity - Ramtenki, Vilas; Raju, D.; Mehta, Urmil J.; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2013)
Two 12-C-glycosyl dodecanoic acids, namely, 1-(alpha-D-mannopyranosyl)-12-dodecanoic acid and 1-(alpha-D-glucopyranosyl)-12-dodecanoic acid were synthesized. Their ability to act as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles is displayed. These Ag C-glycosyl nanoparticles were later utilized to investigate the carbohydrate-lectin interactions. Furthermore, the specificity of mannoside binding to the surface of the Gram negative bacterium Escherichia coli has been utilized to demonstrate the enhanced antibacterial activity of Ag-C-mannosyl nanoparticles towards this bacterium as compared to Ag-C-glycosyl nanoparticles.

Design and synthesis of C-α-D-mannopyranoside linked mesoporous silica nanoparticles - Nechooli, Hemanth K.; Ramtenki, Vilas; Kumar, Chepuri V. Suneel; Prasad, V. B. L.; Ramana, V. Chepuri (Journal of Chemical Sciences, 2025)
Mannose functionalized mesoporous silica nanoparticles (MSNs) offer a promising approach for developing more targeted, effective, and safer cancer therapies. For many of the applications, immobilization of carbohydrates like mannose onto MSNs is a crucial aspect, and in most cases, mannose moieties are connected through O-glycosidic linkages that are susceptible to acidic/enzymatic hydrolysis. To generate a stable mannose-functionalized MSN, we designed a novel C(14)-alpha-mannosylated tetradeca-1-yne. The key steps involved in the synthesis of C-mannosylated alkyne are C1-alkynylation of tri-O-acetyl-D-glucal with 1-trimethylsilyl-tetradec-1-yne, followed by stereoselective dihydroxylation and the isomerization of the internal triple bond to a terminal position. This mannose ligand was then immobilized onto azidopropyl-functionalized SBA-15 through the Cu(I)-catalyzed azide-alkyne click (CuAAC) reaction. Various physical techniques such as low-angle powder XRD, N-2 adsorption isotherms (BET), Fourier transform infrared (FTIR), high-resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FE-SEM), and thermogravimetric analysis (TGA) have been employed to characterize this C-mannosyl SBA-15 silica matrix. We evaluated the binding ability of C-mannosyl SBA-15 nanoparticles by using fluorescein-labelled Con-A as a target protein.
Keywords: C-mannoside; Click reaction; mannose specific proteins; Mesoporous silica nanoparticles; Zipper reaction